Coupling of a Solid Oxide Fuel Cell Auxiliary Power Unit with a Vapour Absorption Refrigeration System for Refrigerated Truck Application. Issue 3 (27th April 2016) - Venkataraman, V.; Pacek, A. W.; Steinberger‐Wilckens, R.
Abstract: Modeling studies have been carried out to investigate coupling of an solid oxide fuel cell auxiliary power unit (SOFC APU) with a small scale NH3 –H2 O based vapour absorption refrigeration system (VARS) for a refrigerated truck/trailer application, by using hot cathode exhaust from the SOFC stack to drive the VARS. A bottom up design and modeling approach has been adopted where the end requirements, cooling load in this case, are identified first followed by upstream modeling of the SOFC and VARS unit. This approach enables design of system/components to meet the desired end requirements rather than compromise or fall short of the desired goal. Initial modeling results show that it is indeed possible to couple an SOFC with a VARS on a small scale (< 10 kW cooling load) for the refrigerated truck application. As this novel strategy utilizes both heat and power from the SOFC it promises a higher total efficiency up to 80% and also removes a significant part of the load from the main diesel engine, thereby leaving the engine to carry out the task of only propelling the vehicle. The excess electrical power from the SOFC could also be used to charge the vehicle batteries.